RANCANG BANGUN “TELEGRAM BOT API” UNTUK LAYANAN SISTEM INFORMASI AKADEMIK DI UNWAHA MENGGUNAKAN METODE LONG POLLING - Fika Ridaul Maulayya; Muhyiddin Zainul Arifin; Tholib Hariono (KH. A. Wahab Hasbullah University, 2019)
Today, the information system needs are not limited to the importance of the information, but the ease and speed of getting the information is a priority that must be fulfilled. This makes many instant messaging applications appear. One of them is a telegram that has features the BOT telegram API, which is a special protocol for connecting information from a system to a user through Instant Messaging. In this research, the researcher used BOT features of the instant messaging application for Academic Information system at KH. A Wahab Hasbullah University includes data KHS, KRS, information dissemination, transcripts of the score, lecture schedules and others. This research used the Long Polling method. This method is used because it can be implemented on a local PC server that is owned by KH. A Wahab Hasbullah University. This telegram BOT has a better speed compared to conventional web versions, this speed testing is done in two steps. First, Use of a BOT of this Telegram has better speeds compared to conventional web version, this speed test is carried out by two steps, 1) the result of BOT telegram using 512 kb Bandwidth with average is 2.98 seconds, conventional web is 5.39 seconds; 2) the result of BOT Telegram using 1 MB bandwidth with average is 2.44 seconds, conventional web is 3.15 seconds.